The Use of the Common Assessment Framework Tool: Empiric Study on the University of Evora (Academic Services) - Nogueiro, Teresa (2012)
As far as our study is concerned, there were several underlying questions deemed relevant: what will the grade of satisfaction of the students and of the internal collaborators be? What kind of diagnosis will the internal collaborators and managers of the Academic Services make? What are the weak and strong points of the Academic Services? Which improvement measures can be devised? Our study aims at being the basis of a self-assessment tool to be systematically undertaken at the Academic Services of the University of Évora, a tool which will provide a means to develop a process of continuous progress, based on a systematic self-assessment. To meet this end, answers to the above questions will have to be given regularly.